2009
DOI: 10.1139/g09-057
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite-based evaluation of Ribes spp. germplasm

Abstract: There is a lack of published microsatellite data which characterizes Ribes spp. To address this, an initial study of simple sequence repeat (SSR) variation was undertaken in 41 cultivars belonging to four species of the genus Ribes to evaluate its genetic variability. The cultivars were collected in Piedmont, northwest Italy, together with one cultivar from Switzerland. Twenty SSRs were screened for amplification and polymorphism. Seven failed to amplify, and therefore the remaining 13 were selected and used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Application of selected SSR markers allowed selection of a core collection of Ribes accessions, which represented 64% of black currant, 80% of red and white currant and 61% of gooseberry alleles identified in the region (Antonius et al, 2012b). A similar SSR marker set was used for characterisation of different Ribes species and interspecific hybrids from North Italy and Switzerland (Cavanna et al, 2009). In contrast to our results, the markers RJL-2, RJL-5, RJL-6 and RJL-7 did not show amplification in Ribes germplasm.…”
Section: Genotyping Of Berry Crop Grmentioning
confidence: 99%
“…Application of selected SSR markers allowed selection of a core collection of Ribes accessions, which represented 64% of black currant, 80% of red and white currant and 61% of gooseberry alleles identified in the region (Antonius et al, 2012b). A similar SSR marker set was used for characterisation of different Ribes species and interspecific hybrids from North Italy and Switzerland (Cavanna et al, 2009). In contrast to our results, the markers RJL-2, RJL-5, RJL-6 and RJL-7 did not show amplification in Ribes germplasm.…”
Section: Genotyping Of Berry Crop Grmentioning
confidence: 99%
“…Simple sequence repeat analysis: Eleven SSR loci (Table 1) were used for the analysis of Ribes ssp. Five were chosen from the list described by Cavanna et al. (2009) and the other six by Brennan et al.…”
Section: Methodsmentioning
confidence: 99%
“…Simple sequence repeat analysis: Eleven SSR loci (Table 1) were used for the analysis of Ribes ssp. Five were chosen from the list described by Cavanna et al (2009) and the other six by Brennan et al (2002), on the basis of the observed polymorphism. Each of the forward primers was 5¢ labelled with 1 of 4 fluorochromes: 6FAM, NED, VIC or PET.…”
Section: Methodsmentioning
confidence: 99%
“…were selected from those tested in Brennan et al (2002) and from the SCRI research centre website (Dundee, UK; www.fruitbreeding.co.uk). We screened the 13 SSR primer combinations selected by Cavanna et al (2009) under the suggested experimental conditions, and when these did not produced results, also under modified conditions (of PCR parameters or reaction mixture). Only four primer combinations produced alleles that could be scored (sequences of the four selected primer combinations are reported in Table S1).…”
Section: Markers For Ssr and Issrmentioning
confidence: 99%
“…In order to investigate the relationships among different accessions of Ribes species, several molecular markers, such as amplified fragment length polymorphisms (AFLP; De Mattia et al 2008), inter-simple sequence repeats (ISSR) and random amplified polymorphic DNA (RAPD; Lanham et al 2000;Kuras et al 2002), anchored microsatellites and simple sequence repeats (SSR; Lanham & Brennan 1998;Brennan et al 2002;Cavanna et al 2009) were tested and/or developed. In particular, De Mattia et al (2008) verified the effectiveness of chloroplast simple sequence repeats (cpSSRs) as a tool to distinguish among different populations of R. uva-crispa L. and R. petraeum Wulfen, as well as to quantify the genetic variability among different individuals from different populations.…”
Section: Introductionmentioning
confidence: 99%